The The Influence Of Mind Mapping Method To Increase Learning Motivation Of VI Grade Students In Citizenship Lessons In Al-Munaya Integrated Islamic Elementary School Academic Year 2021-2022 - Aulannida, Ajeng Munaya; Dahnial, Irfan (Journal of Elementary School Education, 2022)
This study aims to determine the effect of the mind mapping method on increasing the learning motivation of grade VI students of Sdit Al-Munaya for the academic year 2021-2022. The population in this study were all sixth grade students of sdit al-munaya consisting of VIA and VIB for the 2021-2022 academic year. Based on the data obtained by the researcher, there are 60 students of class VI at sdit al-munaya consisting of class VIA and VIB, and the sample in this study is the entire population of 60 students who will be used as samples. randomly selected from each class. The technique used in this research is a quantitative method. From the results of the study, it is known that there is a significant influence between the mind mapping method on the learning motivation of grade VI students of SD sdit al - Munaya (0.590) with a t-test of count >️ie (6,465).